2017
DOI: 10.1007/s10815-017-0915-5
|View full text |Cite
|
Sign up to set email alerts
|

Detrimental effect of maternal and post-weaning high-fat diet on the reproductive function in the adult female offspring rat: roles of insulin-like growth factor 2 and the ovarian circadian clock

Abstract: PurposeWe evaluate the impact of maternal and post-weaning high-fat (HF) diet on ovarian follicular population, steroidogenesis, and gene expression with a focus on the circadian clock system and insulin-like growth factor 2 (Igf2) in adult offspring ovaries, and to elucidate whether a maternal and post-weaning diet confers similar risks.MethodsVirgin Sprague-Dawley rats were fed with normal chow (C) diet or HF diet for 5 weeks before mating, during gestation, and lactation. Female offspring were fed with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Different types of maternal nutritional status have been identified to program adult diseases [2]. And ample evidences demonstrated that maternal exposure to HFD during gestation and lactation has harmful effects on the offspring [20, 21]. In the present study, we focused on the influence of maternal exposure to HFD during gestation only to mimic the excessive gestational weight gain and investigated reproductive potential of the female offspring at PND4 and PND30.…”
Section: Discussionmentioning
confidence: 99%
“…Different types of maternal nutritional status have been identified to program adult diseases [2]. And ample evidences demonstrated that maternal exposure to HFD during gestation and lactation has harmful effects on the offspring [20, 21]. In the present study, we focused on the influence of maternal exposure to HFD during gestation only to mimic the excessive gestational weight gain and investigated reproductive potential of the female offspring at PND4 and PND30.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in germ‐free mice will be instrumental in determining whether gut microbes are necessary or sufficient for the development of the PCOS. Second, both constant light exposure and an HFD have been shown to disrupt the circadian clock (9,10), but influence of constant light plus an HFD on rhythmic expression of clock genes in ovaries has never been reported, to our knowledge. Here, we only detected ovary expression of clock genes at the time of sacrifice.…”
mentioning
confidence: 89%
“…It has been demonstrated that high fat and sugar intake induces alterations in circadian clock function, which seems to be a factor in female reproductive timing, since such changes may harm synchronization between circadian rhythmicity and central or peripheral components. Recently, several studies have shown that high caloric intake leads to premature aging, altered sleep, and disruption in circadian rhythmicity [141][142][143][144]. Highlighting their significance, high-fat diet intake affects the ovarian circadian clock [145].…”
Section: High Fat Diet and Time-restricted Feeding Regulationmentioning
confidence: 99%
“…Highlighting their significance, high-fat diet intake affects the ovarian circadian clock [145]. Circadian core gene expression within ovarian cells revealed changes as a result of maternal and post-weaning high-fat diets [142,145]. Time-restricted feeding (TRF) has been known to prevent body weight gain associated with HFD feeding ad libitum in all genotypes without reducing food intake or increasing activity [146][147][148].…”
Section: High Fat Diet and Time-restricted Feeding Regulationmentioning
confidence: 99%